CORRELATION BETWEEN CHARACTERISTICS AND PARTICIPATION WITH THE SUCCESS OF CULTURAL TOURISM PROGRAM IN NGRAWAN VILLAGE, GETASAN, SEMARANG REGENCY - Advensius Agung Pranata; Tinjung Mary Prihtanti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The cultural tourism program is one of the effective strategies for village development. This study examines the relationship between characteristics and community participation on the success of the dance tourism village program in Tanon hamlet, Ngrawan village, Getasan sub-district, Semarang district. Variables of community characteristics were measured by age, number of family members and education level, while the community participation variable is measured by decision-making participation, implementation, evaluation, and benefit-taking stages participation. The location of the research was carried out in Ngrawan Village, Getasan District. The location of the research location was chosen purposively on the basis of the consideration that the place is one of the villages where the Tourism Village program was successful. The analysis technique used in this research is Spearman rank correlation. The test results show that age (X1), number of family members (X2) and education level (X3) don’t have a significant relationship with the success of the tourism village program (Y), and the decision-making participation variable (X4), implementation (X5), evaluation stage (X6) and benefit taking participation (X7) have a significant relationship with the success of the tourism village program (Y).